Prestressed concrete : a fundamental approach - Nawy, Edward G. (Englewood Cliffs, NJ : Prentice Hall, 1995)
Written by a national and international expert on concrete structures and materials, this second edition of Prestressed Concrete reflects the very latest ACI 318-95 Code provisions and brings you the author's many years of professional and academic know-how.
It includes, for the first time, example solutions in SI Units as well as lists of the ACI equations in SI format.
This book is different from most because its major topics of material behavior, prestress loss, flexure, shear and torsion, and deflection-camber are sequentially self-contained and can be covered in one semester at the senior and the graduate levels. In addition, it is the only book that closely uses and follows procedures given in numerous flowcharts that simplify the understanding and application of the subject in design.
0
Keywords: MCE; Prestressed concrete construction; Prestressed concrete